Improving English reading skills of Grade 2 students using English-Thai consonant sound comparison skills exercises at Thepsathit Wittayakarn School - Somphong, Siriwipha (Academic Journal of Local Development, 2024)
This re-capture aims to study the achievements of English skill development education by using the English-Thai consonant comparison skills of primary school students. 2nd to compare academic achievement between before school and after class using English consonant-Thai comparison skills training of 2nd grade students to develop English reading skills. On the study of English-Thai reading skills development using English-Thai consonant-sound comparison training to be effective according to specified criteria. 70/70/70-Learning satisfaction on English reading skills development using skill training English consonant sound comparison-Thai of 2nd grade students has a total of 29 target are 2nd grade students. Thep Sathit Wittayakarn School This research uses research tools 4 type is-a 6-number learning management plan.Pre-learning test skill training-and satisfaction questionnaire-statistics used in data analysis- Divided into-3-type-is-1)-Basic statistics used in data analysis":-percentage, mean," standard deviation, etc.-2)-comparison statistics used in data analysis - is -* -* -t -test -Dependent 3). Performance analysis statistics of English-Thai consonant comparison skill training using E1/E28-in data analysis "Research found that J 14. Learning achievements on English reading skills development using English-Thai consonant comparison skill training -Thai of 2nd grade students found that pre-school achievement was higher after-0.112. A comparison of academic achievements between pre-school and post-study on English reading skills development using the English-Thai consonant comparison skill training of 2nd grade elementary school students found that the results of comparison of English-Thai reading development before and after teaching using the English-Thai consonant comparison skill training. rise statistically significantly different at the level. .01-The average after school tends to be higher than before school 3.4 Development of English reading capacity-Education of English reading skills Development Grade II students - Using English consonant comparison skills, performance according to the criteria set "70/70/70 - found that the reading skills improved sequentially-each smooth person will have different scores, but if observed, some students practice reading one story well but while another. Learning satisfaction levels on language reading development, English-Thai consonant comparison skills of 2nd graders have been found to be very useful for both learners and instructors. It is that learners can see their progress and measure their abilities as well as deficiencies in teaching and learning. Plan teaching to improve learners effectively.